Undifferentiated Pulmonary Adenocarcinoma of Clear Cells Associated to Hypertrophic Osteopathy in a Dog - Vieira Rossetto, Victor Jose [UNESP]; Rahal, Sheila Canavese [UNESP]; Pardini, Luciana Moura [UNESP]; Fabris, Viciany Erique [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Ribeiro, Sergio Marrone [UNESP] (Univ Fed Rio Grande Do Sul, 2014)
Background: Most of the primary pulmonary tumors in dogs are malignant and from epithelial origin, being bronchioalveolar tumors more prevalent. Adenocarcinoma of clear cells, however, is a very rare pulmonary tumor and its origin is still unknown. It is related to several clinical abnormalities, including hypertrophic osteopathy, an unusual paraneoplastic syndrome characterized by a periosteal reaction along the shaft of long bones. Because of the unusual presentation of the pulmonary adenocarcinoma, the aim of this study was to describe the radiographic, histopathological, and immunohistochemical findings of a dog afflicted with hypertrophic osteopathy secondary to an undifferentiated pulmonary adenocarcinoma of clear cells. Case: A 12-year-old, 45 kg, not castrated male Great Dane dog was presented with painful swelling of all four limbs and moderate respiratory distress. Radiographic examination and computed tomography of the limbs showed palisade-like periosteal bone proliferation involving radius, ulna, femur, patella, tibia, fibula, tarsus, metacarpal, metatarsal and digits, suggesting hypertrophic osteopathy. Radiographic examination and computed tomography of the lungs also showed a round mass well delimited localized in the right diaphragmatic lobe. A lobectomy of the right diaphragmatic lobe and partial lobectomy of accessory lobe were performed. A poorly differentiated clear squamous cell carcinoma was diagnosed by histological examination. An immune-panel of CK5/CK6, CK7, p63 and TTF-1 was used for immunophenotyping. Immunostaining was weakly positive for CK5/CK6 and negative to all others. Therefore, the diagnosis was poorly differentiated clear cell adenocarcinoma. The dog showed improvement in clinical signs seven days after surgery. One month postoperatively, radiographic examination of the limbs showed less intense periosteal reaction and initiation of bone remodeling. Discussion: Primary pulmonary tumors are considered very infrequent in small animals, but its true incidence rate is difficult to establish in animal populations. The histological origin of the tumor in the present case, as verified in the literature, is not well established by histological analysis. In these situations, the immunohistochemistry panel may be useful. The modification of the diagnosis between histological analysis and by immunohistochemistry, among other factors, might be due to transdifferentiation from one phenotype to another at various stages in the neoplastic process. The clear cell appearance observed in this case may be verified in all types of carcinoma due to intracellular accumulation of glycogen, most of which is dissolved during the preparation of paraffin sections. This uncommon neoplasm apparently did not influence the radiographic or tomographic findings of the hypertrophic osteopathy in the present case. The frequency of metastases depends on the histological type of the tumor, being common in the pulmonary adenocarcinoma and usually to tracheobronchial lymph nodes and pulmonary parenchyma. Although in this case the imaging studies did not show metastases to other pulmonary lobes, the histological exams showed metastatic lesions that may be associated to the dog's death after the surgery.
Keywords: dog; lung; pulmonary primary tumor